2019
DOI: 10.1186/s41935-019-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Succession study on forensically important Coleoptera from India: a preliminary study and its forensic implications

Abstract: Background: Coleoptera is the second most important group of entomofauna associated with decomposition, yet little is known about its role in decomposition and postmortem colonization of carcasses in India and other parts of the world. Consequently, a preliminary study was conducted to study the succession of forensically important Coleoptera using goat carrion as an animal model. Results: Five decomposition stages were observed during the experiment. A total of 1174 adult coleopterans belonging to 21 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
5
3
0
Order By: Relevance
“…Our results further showed that Coleoptera species, D. maculatus, T. micans, O. crassicollis , and H. lunatus were the first beetle species to visit the pig carcass during the bloated stage and persisted through to the last stage of decomposition (dry stage) during the warm season with exception of H. lunatus , which was only found during the bloated stage. The presence of these beetles on the carcass as early as bloated stage supports the findings of other several studies that reported the early arrival of Coleoptera species on carcasses ( Early and Goff 1986 , Braack 1987 , Mayer and Vasconcelos 2013 , Singh and Bala 2019 ). According to VanLaerhoven and Anderson (1999) , the presence of these beetles during the bloated stage may be due to seasonal peaks appearance rather than the decomposition stages ( Mabika et al 2014 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results further showed that Coleoptera species, D. maculatus, T. micans, O. crassicollis , and H. lunatus were the first beetle species to visit the pig carcass during the bloated stage and persisted through to the last stage of decomposition (dry stage) during the warm season with exception of H. lunatus , which was only found during the bloated stage. The presence of these beetles on the carcass as early as bloated stage supports the findings of other several studies that reported the early arrival of Coleoptera species on carcasses ( Early and Goff 1986 , Braack 1987 , Mayer and Vasconcelos 2013 , Singh and Bala 2019 ). According to VanLaerhoven and Anderson (1999) , the presence of these beetles during the bloated stage may be due to seasonal peaks appearance rather than the decomposition stages ( Mabika et al 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…The observed similar period of decomposition of carcasses between seasons in this study may have been due to rainfall experienced mostly when the warm season experiment was taking place. According to Lyu et al (2016) rainfall wets the carcass and expel fly maggots from the carcass ( Singh and Bala, 2019 ), and as a result affect the rate at which the carcass decomposes. Archer (2004) also reported that rainfall delay the rate of decomposition by reducing the carcass temperature through evaporative cooling, and hence as the carcass becomes waterlogged, the mass loss become slower.…”
Section: Discussionmentioning
confidence: 99%
“…The scarabaeid beetle Onthophagous sp. reported from the current study has also been reported from other carrion resources such as the chicken liver and dead goat (Tshikae et al 2008;Singh and Bala 2019).…”
Section: Discussionsupporting
confidence: 80%
“…3 Pie-chart showing number of insects species collected per order most carcasses (Shayya et al 2018). It has also been reported on the goat carcass above ground at Kullu, Himachal Pradesh, India (Singh and Bala 2019) and on a buried piece of pork at 60 cm in Punjab, India (Bala and Kaur, 2015). Dung beetles of the subfamily Scarabaeinae are a functionally important group of invertebrates that use both dung and carrion (Vernes et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…The process of decay was articulated in five successive stages (i.e., fresh, bloated, active decay, advanced decay, and remains) as previously described [23]. These results are in line with Singh & Bala, [30] where insect activity increased from the bloated stage, greatest at active decay, and declined during the remains stage due to the scarcity of food sources. The result of our study showed that there was no difference in the rate of decay between clothed and unclothed carcasses throughout the experiments.…”
Section: Discussionsupporting
confidence: 78%